Effect of Phosphatidylcholine on Dyslipidemia and Atherogenic Index in High Fructose Exposed Rats - Surour, Manar A; Ramadhan, Sadiq J; Khudair, Khalisa K (The Iraqi Journal of Veterinary Medicine, 2022)
The purpose of this research was to investigate the beneficial effects of phosphatidylcholine in reducing changes in both lipid and protein profiles in addition to atherogenic index in adult rats with fructose-induced metabolic syndrome. Thirty-six mature Wistar Albino female rats (Rattus norvegicus) (aged 12-15 weeks and weighing 200±10 g) were divided randomly into four groups (G1, G2, G3, and G4); then variable treatments were orally administered for 62 days as follows: G1 (Control group), received distilled water; G2, treated with phosphatidylcholine (PC) orally (1 g/kg BW); G3 (Fr), orally dosed with 40% fructose and 25% fructose mixed with drinking water; G4 (Fr+PC), were also intubated with 40% fructose and 25% fructose in drinking water, and received PC at 1 g/kg BW by oral tube. At the end of the research, specimens were taken by cardio puncture approach after fasting for 8-12 h. Serum was obtained to measure lipid criteria (total serum cholesterol, triacylglycerol, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, very low-density lipoprotein-cholesterol, non-high-density lipoprotein-cholesterol, and Atherogenic index) and protein profile (total protein, albumin, and globulins). The results showed that the occurrence of dyslipidaemia (hypercholesterolemia, triacyleglycerolemia) increase in low density of lipoprotein-cholesterol, very low-density lipoprotein-cholesterol, no-high density lipoprotein-cholesterol concentrations and atherogenic index and reduce the concentration of high-density lipoprotein-cholesterol) in fructose treated animals in addition to disturbance in protein profile (lowered in total protein and globulins level).PC treatment resulted in decreased changes in lipid profile, protein profile, and atherogenic index in rats, whereas fructose induced metabolic syndrome. In conclusion, using Phosphatidylcholine treatment in rats may reduce the changes of lipid and protein profiles and atherogenic index while fructose may lead to metabolic syndrome.